2017
DOI: 10.1016/j.apergo.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Job rotation designed to prevent musculoskeletal disorders and control risk in manufacturing industries: A systematic review

Abstract: To better understand job rotation in the manufacturing industry, we completed a systematic review asking the following questions: 1) How do job-rotation programs impact work-related musculoskeletal disorders (MSDs) and related risk control for these MSDs, as well as psychosocial factors? and 2) How best should the job rotation programs be designed? We searched MEDLINE, EMBASE, Business Source Premier, ISI Web of Knowledge, CINAHL, PsyINFO, Scopus, and SciELO databases for articles published in peer-reviewed jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 41 publications
0
80
0
9
Order By: Relevance
“…Job rotation programs have been tested as well, in the wake of the lean manufacturing movement or in attempts to manage exposure to factors causing musculoskeletal injuries. In the latter case, the results are not convincing, according to the most recent review of the literature [6]. The inadequacy of these strategies has been noted previously [7].…”
Section: Introductionmentioning
confidence: 47%
See 2 more Smart Citations
“…Job rotation programs have been tested as well, in the wake of the lean manufacturing movement or in attempts to manage exposure to factors causing musculoskeletal injuries. In the latter case, the results are not convincing, according to the most recent review of the literature [6]. The inadequacy of these strategies has been noted previously [7].…”
Section: Introductionmentioning
confidence: 47%
“…providing pauses or breaks) or allotting vehicles, equipment and tools to workers [21]. Existing job rotation programs are focused primarily on managing biomechanical and organizational risks [6]. Analytical models focused on integrating these two perspectives include factors such as details of work contracts (work shifts, part-time, flexible scheduling), worker preferences, level of production, skills, training, physical capacity and experience, as well as the effects of learning [13,[21][22][23][24], exposure to noise, physical workload or anthropometric data [13,22,23,[25][26][27][28][29], age [11,14] and cognitive ergonomic factors such as human reliability or task complexity [27,30,31].…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the potential benefits of job rotation for reducing exposure and preventing musculoskeletal disorders, as widely propagated among industrial managers and described in the literature, two recent systematic reviews reported weak evidence for job rotation effectiveness and indicated that it increases exposure 8 9. Only the study of Padula et al 8 focused on the concept of job rotation proposed for manufacturing industries.…”
Section: Introductionmentioning
confidence: 99%
“…Only the study of Padula et al 8 focused on the concept of job rotation proposed for manufacturing industries. It demonstrated that few studies have evaluated the benefit of job rotation to musculoskeletal health in industrial environments.…”
Section: Introductionmentioning
confidence: 99%